The Growth and EPA Synthesis of Shewanella oneidensis MR-1 and Expectation of EPA Biosynthetic Pathway - Jeong, Young-Su; Song, Sang-Kyu; Lee, Su-Jin; Hur, Byung-Ki (Biotechnology and bioprocess engineering, 2006)
Shewanella oneidensis MR-1 has the ability to inhale certain metals and chemical compounds and exhale these materials in an altered state; as a result, this microorganism has been widely applied in bioremediation protocols. However, the relevant characteristics of cell growth and biosynthesis of PuFAs have yet to be thoroughly investigated. Therefore, in this study, we have attempted to characterize the growth and fatty acid profiles of S. oneidensis MR-1 under a variety of temperature conditions. The fastest growth of S. oneidensis MR-1 was observed at $30^{°}C$, with a specific growth rate and doubling time of $0.6885h^{-1}\;and\;1.007 h$. The maximum cell mass of this microorganism was elicited at a temperature of $4^{°}C$. The eicosapentaenoic acid (EPA) synthesis of S. oneidensis MR-1 was evaluated under these different culture temperatures. S. oneidensis MR-1 was found not to synthesize EPA at temperatures in excess of $30^{°}C$, but was shown to synthesize EPA at temperatures below $30^{°}C$. The EPA content was found to increase with decreases in temperature. We then evaluated the EPA biosynthetic pathway, using a phylogenetic tree predicted on 16s rRNA sequences, and the homology of ORFs between S. oneidensis MR-1 and Shewanella putrefaciens SCRC-2738, which is known to harbor a polyketide synthase (PKS)-like module. The phylogenetic tree revealed that MR-1 was very closely related to both Moritella sp., which is known to synthesize DHA via a PKS-like pathway, and S. putrefaciens, which has been reported to synthesize EPA via an identical pathway. The homology between the PKS-like module of S. putrefaciens SCRC-2738 and the entire genome of S. oneidensis MR-1 was also analyzed, in order to mine the genes associated with the PKS-like pathway in S. oneidensis MR-1. A putative PKS-like module for EPA biosynthesis was verified by this analysis, and was also corroborated by the experimental finding that S. oneidensis MR-1 was able to synthesize EPA without the expression of $dihomo-γ-linoleic$ acid (DGLA) and arachidonic acid (AA) formed during EPA synthesis via the FAS pathway.